2008
DOI: 10.1249/mss.0b013e318189422b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 4-Month Recruit Training Program on Markers of Bone Metabolism

Abstract: Military training increased bone formation and resorption markers in 2 months, suggesting rapid onset of strenuous exercise accelerates bone turnover similarly in men and women. Although bone turnover markers were higher in men than women, bone formation status may be related to aerobic fitness and serum calcium independent of gender and may be affected by small changes in endocrine regulators related to nutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
68
3
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 38 publications
14
68
3
13
Order By: Relevance
“…Previous studies have reported conflicting findings with regards to longitudinal changes in bone turnover markers during military training, as well as with respect to differences between stress fracture cases and controls [19][20][21][22]. Therefore the relevance of bone turnover markers in predicting stress fracture risk remains unclear.…”
Section: Bone Turnover Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported conflicting findings with regards to longitudinal changes in bone turnover markers during military training, as well as with respect to differences between stress fracture cases and controls [19][20][21][22]. Therefore the relevance of bone turnover markers in predicting stress fracture risk remains unclear.…”
Section: Bone Turnover Markersmentioning
confidence: 99%
“…Conversely, a study in male (n = 58) and female (n = 155) US Marine recruits measured higher concentrations of the bone resorption marker deoxypyridinoline (DPD) at the end of an 11 week training programme compared with before the start of the training programme [36]. Evans et al observed higher concentrations of serum CTx at middle and end time points, of a 4-month programme of basic recruit training, compared with baseline concentrations in n = 58 male military recruits [21]. Concurrent analyses of bone formation and resorption markers during training, in the population of interest, may help to elucidate the mechanisms associated with bone turnover during military training.…”
Section: Bone Resorptionmentioning
confidence: 99%
“…For univariate comparisons, the 12-week values groups were compared to each other with analysis of covariance with the baseline value as a covariate. The preliminary statistical power analysis was based on previous studies using bALP as a bone marker (Evans et al 2008;Lester et al 2009;Menkes et al 1993;Shibata et al 2003). The literature indicated large effect sizes (ES [ 2) in association with exercise interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Ainda, o metabolismo do cálcio sofre profundas modificações em resposta ao treinamento físico. Evans et al (50) identificaram elevação significativa dos marcadores bioquímicos do turnover de cálcio após quatro meses de treinamento físico, em homens e mulheres. Esse aumento comprova a importância da ingestão dietética desse nutriente para que sejam mantidos os processos de construção óssea, contração muscular e ainda a atividade de diversas enzimas dependentes de cálcio.…”
Section: Discussionunclassified